From the Front to the West Coast : the Recollections of the Finnish War Veterans in Vancouver - Kelly, Leena (Siirtolaisuusinstituutti, 2014)
This is a story of a country, Finland, at war as told through the experiences of veterans. The book starts off with the Winter War, and continues on to the two other wars that followed, revealing history through personal experience as well as the consequences to the country as a whole; tragedy and hope. However, after the war, these veterans left the country they had so fiercely defended to start a new life in Canada. This unique project, a historical snapshot, searches for answers as to why they left Finland for Canada. Did the wars influence their decision? Despite the seriousness of the topic, sprinklings of humour in the stories lighten the mood. ”From the Front to the West Coast is a cultural achievement, because it attests the vitality of memories from decade to decade. The documentary is a reminder of how the memories of where you lived during childhood and youth endure forever in the human mind. It is amazing to witness the significance of being Finnish, and the significance of war memories, for these veterans.” — Mika Kulju, Finnish historian and non-fiction author of Frozen Hell – The Legend and the Tragedy of Raate Road. Prologue 1. History of Finland-Canada Relations 2. The Winter War 2.1. Living and Waiting in Fear 2.2. Evacuating Karelia 2.3. “Now the War Has Broken Out!” 2.4. Home by the Airport 2.5. Molotov’s Cocktail 3. The Continuation War 3.1. On the Offence 3.2. Armoured Ship Ilmarinen’s Fate 3.3. The Happy Little Sister 3.4. She was an Army Driver 3.5. A Soldier’s Christmas 3.6. Conscientious Objector 3.7. Following Orders 3.8. Sweeping Mines 3.9. Battle on the Island 3.10. “For Us Karelians, We Had to” 3.11. Female Russian Soldier 3.12. Almost a Prisoner of War 3.13. Unforgettable Food Pick-Up 3.14. “Korohoroman” 4. The Lapland War 5. Immigration from Finland 5.1. Far West 5.2. No More War 5.3. Nursing in Canada 5.4. “That Girl Goes” 5.5. Adventures and Shortages 5.6. Canada is Looking for Immigrants 5.7. In His Father’s Footsteps 5.8. Hard Labour 5.9. Veteran at the Age of Eighteen 5.10. ...